2021
DOI: 10.1155/2021/1418281
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Clinical Effect of Music Combined with Hypnosis on Labor Analgesia Based on Data Mining

Abstract: The objective of this paper is to study the curative effect of music combined with hypnosis on labor pains during childbirth. Based on the algorithm of data mining, we randomly selected 100 women who delivered babies in obstetric units from October 2020 to June 2021, set the control group and the observation group, obtained the relevant clinical data through comparison, and analyzed the value of music combined with hypnotic analgesia midwifery in obstetrics. The results showed that the number of spontaneous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%